Role of bitter contributors and bitter taste receptors: a comprehensive review of their sources, functions and future development - Xinyue Zhou; Han Wang; Ming Huang; Jin Chen; Jianle Chen; Huan Cheng; Xingqian Ye; Wenjun Wang; Donghong Liu (Food Science and Human Wellness)
Bitterness, one of the 5 “basic tastes”, is usually undesired by humans. However, abundant literature reported that bitter fruits and vegetables have beneficial health effects due to their bitter contributors. This review provided an updated overview of the main bitter contributors of typical bitter fruits and vegetables and their health benefits. The main bitter contributors, including phenolics, terpenoids, alkaloids, amino acids, nucleosides and purines, were summarized. The bioactivities and wide range of beneficial effects of them on anti-cancers, anti-inflammations, anti-microbes, neuroprotection, inhibiting chronic and acute injury in organs, as well as regulating behavior performance and metabolism were reported. Furthermore, not only did the bitter taste receptors (taste receptor type 2 family, T2Rs) show taste effects, but extra-oral T2Rs could also be activated by binding with bitter components, regulating physiological activities via modulating hormone secretion, immunity, metabolism, and cell proliferation. This review provided a new perspective on exploring and explaining the nutrition of bitter foods, revealing the relationship between the functions of bitter contributors from food and T2Rs. Future trends may focus on revealing the possibility of T2Rs being targets for the treatment of diseases, exploring the mechanism of T2Rs mediating the bioactivities, and making bitter foods more acceptable without getting rid of bitter contributors.